An exploration of prospective memory components and subtasks of the Memory for Intentions Test (MIST). Issue 3 (15th March 2020) - Belmar, Mariana; Gladwin, Thomas E.; Reis, Lurdes; Pinho, Maria S.; Silva, Dina; Nunes, Maria Vânia; Raskin, Sarah; de Mendonça, Alexandre; Pereira, Antonina
ABSTRACT: Introduction : Prospective Memory (PM), the ability to execute future intentions, decreases with age and memory-related disorders and may be an early predictor of dementia. The Memory for Intentions Test (MIST) allows the assessment of multiple aspects of PM using a range of subtasks. The current study evaluated and explored a Portuguese version of the MIST and its subtasks. Method : Forty-one patients with Mild Cognitive Impairment (MCI) and forty healthy participants performed the MIST, neuropsychological tests and questionnaires. Analyses were performed testing relationships between MCI and PM components of the MIST, and differences between subtasks of the test were explored. Results : Reliability of the PM component was acceptable within the patient group, but not within the control group. PM components were significantly lower in the MCI patients, but this effect was dependent on subtasks. Groups differed most strongly at shorter intervals. PM scores predicted MCI status. Correlations were found between PM components and cognitive functioning scales. Conclusions : The Portuguese version of the MIST seems suitable for use in clinical practice and research. MCI is differentially related to different PM components and subtasks of the MIST.